2017
DOI: 10.1007/s11010-017-3166-y
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 regulation affects the treatment of glucocorticoid for pancreatitis-induced lung injury

Abstract: Glucocorticoids are commonly used for the treatment of pancreatitis and complicated acute lung injury and help to reduce the mortality rates of both. The effect of gene variants in heat shock protein 90 (Hsp90), a key chaperone molecule of the glucocorticoid receptor (GR), on the therapeutic effect of glucocorticoids is unclear. Our study aims to investigate the different susceptibility to glucocorticoid treatment in BALB/c and C57BL/6 mice carrying different Hsp90 genotypes in an animal model of pancreatitis-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…These data suggested XYS could protect PMs from CORT-induced stress by inhibiting the elevated GR protein level from being transported into the nucleus. Previous reports also showed that HSP90 could assist the internuclear transfer of GC-GR complex, then GC-GR complex could bind to the GR element (GRE) and induce C D E F the expression of the target genes (13,28). When released from HSP90, the activity of GR's transportation into the nucleus was enhanced.…”
Section: Discussionmentioning
confidence: 97%
“…These data suggested XYS could protect PMs from CORT-induced stress by inhibiting the elevated GR protein level from being transported into the nucleus. Previous reports also showed that HSP90 could assist the internuclear transfer of GC-GR complex, then GC-GR complex could bind to the GR element (GRE) and induce C D E F the expression of the target genes (13,28). When released from HSP90, the activity of GR's transportation into the nucleus was enhanced.…”
Section: Discussionmentioning
confidence: 97%
“…Performance, detection and reporting bias: No blinding, no stated histopathology scoring system, no statistical evaluation, seems to be conclusions based on subjective evaluation. No drop-outs Very small (6/6) Zhao et al [ 64 ] Mice Controlled trial III Good, all male, similar age mice of 2 genotypes High Selection bias: No randomisation stated. Performance, detection and reporting bias: No blinding stated, histopathological changes of the pancreas was not included in the aims, but shown by photos and not commented on.…”
Section: Search Strategymentioning
confidence: 99%
“…Only 1 study [ 38 ] described the method of randomisation. Eight studies were categorised as nonrandomised controlled trials, with 4 involving canines [ 57 60 ] and 4 involving rodents [ 61 64 ]. Two human studies were categorised as retrospective case control studies [ 37 , 65 ], and 1 human study was categorised as a case series [ 66 ] (Tables 1 and 2 ).…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations